2020
DOI: 10.2147/ott.s266067
|View full text |Cite|
|
Sign up to set email alerts
|

<p>LncRNA RNF144A-AS1 Promotes Bladder Cancer Progression via RNF144A-AS1/miR-455-5p/SOX11 Axis</p>

Abstract: Background Bladder cancer (BC) is the most commonly occurring malignant tumor of the urinary system worldwide. Long non-coding RNAs (lncRNAs), including lncRNA RNF144A-AS1 (RNF144A-AS1), perform an oncogenic role in BC progression. However, how RNF144A-AS1 is regulated in BC has not been fully investigated, and its role in BC is mostly obscure. In this study, we explore its role in BC progression. Materials and Methods The expression level of RNF144A-AS1 in BC tissues w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…According to some studies RNF144A-AS1, also known as GRASLND, is highly expressed in bladder cancer, and overexpression of the transcript is correlated with poor prognosis. The same study also observed that the knockdown of RNF144A-AS1 eventually inhibited cell proliferation, migration, and invasion in J82 and 5637 cell lines, in addition xenograft growth of cells was reduced compared to negative control in nude mice [46,47]. Another study highlighted RNF144A-AS1 as an important regulator of mesenchymal stem cell chondrogenesis [48].…”
Section: Discussionmentioning
confidence: 76%
“…According to some studies RNF144A-AS1, also known as GRASLND, is highly expressed in bladder cancer, and overexpression of the transcript is correlated with poor prognosis. The same study also observed that the knockdown of RNF144A-AS1 eventually inhibited cell proliferation, migration, and invasion in J82 and 5637 cell lines, in addition xenograft growth of cells was reduced compared to negative control in nude mice [46,47]. Another study highlighted RNF144A-AS1 as an important regulator of mesenchymal stem cell chondrogenesis [48].…”
Section: Discussionmentioning
confidence: 76%
“…RNF144A-AS1, also named as Glycosaminoglycan Regulatory Associated Long Non-coding RNA (GRASLND), was first identified as a regulator of mesenchymal stem cell chondrogenesis [ 36 ]. In bladder cancer (BCa), it was reported that an RNF144A-AS1-based nomogram could effectively predict the prognosis of patients with BCa, and RNF144A-AS1 could promote proliferation, migration, and invasion of bladder cancer cells [ 37 , 38 ]. Consistent with above researches, our study also detected an increased expression of RNF144A-AS1 in GC tissues and also suggested strong associations of RNF144A-AS1 with poor prognosis and later-stage diseases in patients with GC.…”
Section: Discussionmentioning
confidence: 99%
“…ZNFX1-AS1 targeting miR-193a-3p/SDC1 regulates cell proliferation, migration, and invasion of BCa cells [ 47 ]. RNF144A-AS1 enhances the malignant behaviors of BCa cells via the miR-455-5p/SOX11 axis [ 48 ]. TUG1 inhibits miR-29c expression to promote cancer cell proliferation, metastasis [ 49 ].…”
Section: Cell Proliferationmentioning
confidence: 99%